Sequence homologies in the protamine gene family of rainbow trout. - Aiken, J M (1983)
We have sequenced five different rainbow trout protamine genes plus their flanking regions. The genes are not clustered and do not contain intervening sequences. There is an extremely high degree of sequence conservation in the coding and 3' untranslated regions of the gene. Downstream sequences exhibit little homology though conserved regions are found 250 base pairs 3' to the gene. There are four regions upstream of the gene that are highly conserved in the six clones, including the canonical Goldberg - Hogness box which is 45 base pairs 5' to the coding region. A second homologous region is found 90 bases upstream. Although in the same approximate location as the CAAT box found upstream of other genes, it does not contain the canonical CAAT sequence. Further upstream of the protamine genes at -115 there is an A-T rich sequence while a 25 base pair conserved sequence is located 150 bases upstream. In addition we report the presence of a potential Z-DNA region of predominantly A-C repeats approximately one kilobase downstream of one of the genes.